2002
DOI: 10.1002/1527-2648(200204)4:4<169::aid-adem169>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Concepts for Integrating Plastic Anisotropy into Metal Forming Simulations

Abstract: Modern metal forming and crash simulations are usually based on the finite element method. Aims of such simulations are typically the prediction of the material shape, failure, and mechanical properties during deformation. Further goals lie in the computer assisted lay‐out of manufacturing tools used for intricate processing steps. Any such simulation requires that the material under investigation is specified in terms of its respective constitutive behavior. Modern finite element simulations typically use thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…The evolution of the dislocations is mapped separately for each slip system according to the dyadic formulation of the crystal plasticity kinematics. [14] The Orowan equation serves as the kinetic equation of state and the evolution laws for the immobile SSDs are formulated as rate equations based on distinct dislocation processes such as lock formation or annihilation. Constitutive parameters for the copper single crystal were taken from Zaafarani et al [15] , Appendix A.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The evolution of the dislocations is mapped separately for each slip system according to the dyadic formulation of the crystal plasticity kinematics. [14] The Orowan equation serves as the kinetic equation of state and the evolution laws for the immobile SSDs are formulated as rate equations based on distinct dislocation processes such as lock formation or annihilation. Constitutive parameters for the copper single crystal were taken from Zaafarani et al [15] , Appendix A.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…It will be shown that such an approach allows to reduce the number of crystal orientations significantly. In contrast to other texture component models [28,22], the present approach takes into account the half-width of the texture components during the computation of the stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Thermo-mechanically processed metallic materials commonly display mechanical anisotropy [7]- [10]. This has been examined extensively, by analysing the effects of microstructural parameters and texture.…”
Section: Influence Of Plate Rolling On Mechanical Anisotropy Of the Coilmentioning
confidence: 99%